Economics Teaching Materials Short Story Text For Class XI Students of SMA Negeri 1 Palimanan, Cirebon District - Yati Yati; Zuhri Saputra Hutabarat (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
This study aims to design short story text economics teaching materials and how the results of the implementation of short story text economics teaching materials for class XI students of SMA Negeri 1 Palimanan. This research method is to use qualitative research with analytic descriptive method. The research location was carried out at SMA Negeri 1 Palimanan, Cirebon Regency. The results showed that based on the implementation of short story text teaching materials for class XI students of SMA Negeri 1 Palimanan, namely the results of the student response questionnaire showed a satisfactory response, meaning that students could well accept short story teaching materials, on average students were quite good at understanding the contents of the material. teaching materials and can help teaching materials in teaching and learning activities in class, especially in short story material. Students hope that teaching materials that are made according to the needs of students like this can continue to be developed to support learning materials. Students feel interested and easily understand the material because it is neatly arranged and the front cover illustrations of the books are adjusted to the colors that make students interested in reading them, the use of color in teaching materials is very important so that students when reading material or assignments do not get bored and want to work on the material. teach it. The language used in textbooks is in accordance with the readability level of high school students and in terms of illustrations and pictures in teaching materials it really helps students' interest in reading. The teaching materials presented make it easier for students to understand the material because it is adapted to the curriculum so that it facilitates learning activities, especially short story text material.